Dari Konformitas Ke Normalisasi: Analisis Sosiologi Kriminal Terhadap Pelecehan Mahasiswi Di Lingkungan Perguruan Tinggi - Risandi; Syalia Sefitriani; Andy Suhendra; Hayati Pelita; Soni; Endri Bagus Prastyo (Jurnal Neo Societal, 2026)
This research aims to analyze how group conformity develops into a form of normalization of verbal sexual display behavior in higher education environments in Indonesia through the perspective of Criminal Sociology. This research uses a qualitative descriptive method with an analytical literature study approach through academic literature, relevant regulations, as well as cases that became public attention in April 2026, namely the case of the student conversation group at the Faculty of Law, University of Indonesia and the controversy over the song "Erika" performed by the Mining Student Association of the Bandung Institute of Technology. The analytical framework for this research uses anomie theory, the concept of toxic masculinity, a patriarchal perspective, as well as rape culture and victim blaming. The research results show that verbal and digital sexual understanding in the campus environment is formed through a group conformity mechanism which takes place gradually until it develops into an unwritten norm within the group. This research concludes that the normalization of sexual conversations in the campus environment occurs through three stages: initial conformity, consent without sanctions, and internalization as an unwritten group norm. This research further encourages strengthening the preventive and active role of the PPKS Task force, integrating gender education in the academic environment, as well as enforcing strict and transparant sancionts in the tertiary environment